Enlightening of the low-dimensional high-TC superconductivity: bond contraction and electron dual polarization [低维高温超导的启示: 键收缩与电子双重极化] - Sun, Chang Qing (2022)
Electron-phonon interaction that couples the carriers for the Bose-Einstein condensation and the nature and configuration of the O-Cu chains and O-Cu planes that accommodate carriers are key issues to the cuprite high-TC superconductivity discovered in 1986. However, the new kind of high-TC superconductivity is beyond the description of the conventional Bardeen-Cooper-Schrieffer (BCS) theory. Here we address these two issues based on the bond order-length-strength correlation and nonbonding electron polarization (BOLS-NEP) notion for the effect of atomic undercoordination and the hydrogen bond (O:H-O equivalent of O:Cu-O) cooperativity and polarizability (HBCP) premise for water ice with involvement of electron lone pairs ":" interactions. First, a Cup:O:Cup dipolar chain is formed by connecting a series of tetrahedrons made of two Cu+ ions and two Cup dipoles surrounding the center O2-. The O-Cu(110) plane includes three sublayers. The first one is made of alternative rows of Cu0 vacancies and the Cup:O:Cup dipolar chain with dipoles pointing out the surface; the second sublayer is formed by O2- whose lone pairs polarize the dipoles and squeeze out the missing rows of Cu atoms, and the third sublayer is made of Cu+. However, the O-Cu(001) plane shows a different manner of the sublayers. The first sublayer is made of Cup, Cu0, and Cu2+, and the third sublayer of Cu+ and Cu. The O2- bonds to the Cu+ and polarizes the Cu to form the oppositely-coupled dipoles on the Cu(001) surface. The O-Cu bonding proceeds in four discrete stages: O2 bonds to one Cu to form the Cu2+-2O- and then each O- bonds to its neighboring Cu in the second layer to form the twin tetrahedron with the production of the lone pairs. The introduction of O to Cu host creates valence density features of the O-Cu bonding, lone pair nonbonding, the dipolar antibonding above EF, and electron holes. Second, atomic undercoordination of the O-Cu chains and the O-Cu planes shortens and stiffens the local O-Cu bond and lengthens and weakens the O:Cup nonbonding interactions associated with further enhancement of the Cup dipoles polarization, this process is the same as the O:H-O bond relaxation and polarization occurred to the skins of water and ice. Last, the electronphonon interaction is realized by the undercoordination-induced bond relaxation and the dual polarization by lone pairs and bond contraction. The dual polarization weakens the O:Cup interactions and lowers the vibration frequency of the Cup, reducing the effective mass of the CuP electrons with high group velocity for carrier transport between the adjacent O-Cu planes that are made of atomic vacancies and dipoles. The self-entrapment of the core and bonding electrons, and the localized polarization and O:Cup weakening may describe the effect of electron-phonon coupling. The discovered "attraction force" between electrons along the Cu-O chain may fingerprint the effect of atomic undercoordination-induced bond contraction. The understandings of the dual polarization by oxidation and atomic undercoordination of carriers and the electron-phonon interaction may extend to devising the low-dimensional high-TC superconductivity and the edge states polarization for the topological insulator superconductivity. The BOLS-NEP and HBCP regulations could be essential ingredients for the carrier generation and their interactions, which shall play certain substantial roles in the new types of superconductivity.